The dark hours [large type] - Connelly, Michael, 1956- (2021)
"Has a killer lain dormant for years only to strike again on New Year's Eve? LAPD Detective Renée Ballard and Harry Bosch team up to find justice for an innocent victim in the new thriller from #1 New York Times bestselling author Michael Connelly"--